2005
DOI: 10.1021/jm0491039
|View full text |Cite
|
Sign up to set email alerts
|

Protein Farnesyltransferase Inhibitors Exhibit Potent Antimalarial Activity

Abstract: New therapeutics to combat malaria are desperately needed. Here we show that the enzyme protein farnesyltransferase (PFT) from the malaria parasite Plasmodium falciparum (P. falciparum) is an ideal drug target. PFT inhibitors (PFTIs) are well tolerated in man, but are highly cytotoxic to P. falciparum. Because of their anticancer properties, PFTIs comprise a highly developed class of compounds. PFTIs are ideal for the rapid development of antimalarials, allowing "piggy-backing" on previously garnered informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
144
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(149 citation statements)
references
References 26 publications
3
144
0
Order By: Relevance
“…The tetrahydroquinoline series of FTIs, originally developed by Bristol-Myers Squibb as anticancer agents, are the most promising antimalarial FTIs reported so far. They kill parasites in culture in the low nanomolar range and can cure rodents infected with malaria when dosed orally 138 . This illustrates the 'piggyback medicinal chemistry' approach of taking advantage of work done by large pharmaceutical companies and extending it for use in treating neglected diseases.…”
Section: Ftis As Tropical Parasitic Disease Therapeuticsmentioning
confidence: 99%
“…The tetrahydroquinoline series of FTIs, originally developed by Bristol-Myers Squibb as anticancer agents, are the most promising antimalarial FTIs reported so far. They kill parasites in culture in the low nanomolar range and can cure rodents infected with malaria when dosed orally 138 . This illustrates the 'piggyback medicinal chemistry' approach of taking advantage of work done by large pharmaceutical companies and extending it for use in treating neglected diseases.…”
Section: Ftis As Tropical Parasitic Disease Therapeuticsmentioning
confidence: 99%
“…The 50 kDa proteins were analyzed and found to be modified by a farnesyl group; the lower molecular mass proteins, however, were found to be geranylgeranylated, presumably after the conversion of farnesol into both farnesyl pyrophosphate and geranylger-anyl pyrophosphate. Our group later showed that the 50 kDa farnesylated proteins, but not the lower molecular mass geranylgeranylated proteins, were specifically inhibited by PFTIs (11). Using synchronized P. falciparum, Chakrabarti et al (5) demonstrated the stage-specific incorporation of prenylation precursors, the highest amount of incorporation occurring in the trophozoite (mid erythrocytic stage) to schizont (cell division stage) and schizont to ring (early erythrocytic stage) transition states in the erythrocytic life cycle of the parasite.…”
Section: Pft In Pathogenic Protozoamentioning
confidence: 96%
“…The isoprenyl lipid modification of proteins has been shown to be critical for various cellular activities in mammals and yeast, including proliferation and apoptosis (8,9). Growth of the protozoan parasites has been shown to be severely impaired by the inhibition of protein farnesylation compared with mammalian cells, suggesting high potential of the enzyme protein farnesyltransferase (PFT) as an antiparasitic drug target (5,(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…T. brucei and malaria parasites show high sensitivity to inhibition of PFT compared to mammalian cells [20][21][22][23]. We previously reported that potent PFT inhibitors are highly effective in blocking growth of malaria parasites and T. brucei bloodstream forms, suggesting the opportunity to develop PFT inhibitors as therapeutics for diseases caused by these parasites [22][23][24][25]. It is likely that PFT inhibitors are selectively toxic to these protozoan parasites because of absence of PGGT-I or lack of alternative modification of critical farnesylated proteins in the parasites.…”
Section: Introductionmentioning
confidence: 99%